Prevalensi dan karakteristik morfologis Ascaris suum pada babi ras lokal dan landrace di Kota Kupang - Erdian C Putra; Julianty Almet; Aji Winarso (Jurnal Veteriner Nusantara, 2019)
Pigs are important livestock commodities of the community in the East Nusa Tenggara. Pigs in East Nusa Tenggara sussceptible to endoparasite disease because of traditionally maintained. One of worm parasites that attack the pigs are Ascaris suum. The purpose of this study to determine the prevalence and morphological characteristic in 10 pigs local races and 10 landrace race. The results showed from 12 pigs local races only 1 had infected of Ascaris suum with prevalence of 8,3%. Of the 142 pigs landrace race are found 10 pigs had infected of Ascaris suum with prevalence of 7,04%. According to worm count, the value of Ascaris suum infection in race lokal pigs relatively higher with burden parasitism 72 worm per pig compared to landrace pig races with infection load average of 1,5 worm per pig. Morphological examination of Ascaris suum in pigs local race shows the length and diameter of female worms 25,25(±3,23) cm and 3,37(±0,91) mm and the length and diameter of the male worms 29,13(±3,84) cm and 5,03 (±1,28)mm and the length and diameter of the male worms 20,62(±2,37)cm and 3,02 (±1,59)mm. Ascaris suum male has a reddish brown color and in Ascaris suum females have a pale brown color (white). the concluded of this study Ascaris suum in kota kupang has the morphological characteristics that are not much different with the literature, with the highest prevalence occurs in pigs local races